Controlling ligand binding for tunable and switchable catalysis: cation-modulated hemilability in pincer-crown ether ligands - Miller, Alexander J. M (Dalton transactions : an international journal of inorganic chemistry, 2017)
Methods for in situ reversible control over ligand binding processes at transition metal complexes can enable advances in switchable and tunable catalysis. After a brief overview of different approaches to controlling ligand binding, this Perspective details the development of "pincer-crown ether" ligands that contain a rigid pincer backbone and a hemilabile aza-crown ether unit that enables cation-modulated hemilability. Applications of pincer-crown ether complexes in small molecule activation and catalysis are discussed, culminating in a set of design principles for ligands capable of cation-modulated ligand binding. The development of cation-responsive "pincer-crown ether" complexes featuring tunable hemilability is reviewed in the context of switchable and tunable catalysis.